Effects of protein solubilisation and precipitation pH values on the functional properties of defatted wheat germ protein isolates. (14th March 2013) - Liu, Fengru; Chen, Zhengxing; Wang, Li; Wang, Ren
Summary Wheat germ protein isolates were prepared from defatted wheat germ flour using alkaline solubilisation and acid precipitation. A central composite design with two independent variables (solubilisation pH and precipitation pH) and bivariate correlations was selected for the correlation analysis of the protein separation conditions and the functional properties. The results showed that the protein yield (Y) and functional properties of isolates, such as water absorption (WA) and fat absorption (FA), were sensitive to both solubilisation pH and precipitation pH, whereas the emulsification was sensitive to only solubilisation pH. Emulsifying activity (EA) and FA of isolates showed a high positive correlation with yield. Gel electrophoresis analysis of protein fractions gave evidence to the compositional changes between proteins isolated under different conditions, highly alkaline conditions result in the degradation of protein chains and formation of toxic compounds. Surface hydrophobicity suggested that proteins tend to be more denatured when solubilised at highly alkaline conditions. These conformational and compositional changes due to different protein separation conditions have contributed to the changes in functional properties of protein isolates.